I Kalasha del Hindu Kush: ricerche linguistiche e antropologiche - Di Carlo, Pierpaolo (Premio Tesi di Dottorato, 2010)
The Kalush are the last Kafirs (pagans) of Hindu Kush and speak an Indo-European language, which makes them a particularly precious resource for the Indo-European scholar. This thesis offers an in-depth study of their language and of some aspects of their culture. Starting from the data collected during a field study in the least well-known of the three Kalasha valleys, on the border between Pakistan and Afghanistan, the author proposes a contrastive analysis of the everyday language and that used for poetry. This analysis, and the mass of ethnographic data considered, enable the author to identify the socio-cultural reasons behind certain linguistic choices that can be observed in the poetic discourse, thus bringing to light the essence of the relations between language and culture.